CONSUMER BEHAVIOUR ON THE WINE MARKET IN NITRA REGION - Katarína Kleinová; Ľudmila Nagyová; Petra Waldnerová (Polityki Europejskie, Finanse i Marketing)
Today, no businesses can afford to ignore marketing, because it plays a very important role in every company. Last years entrepreneurs have started to feel the need of promotion their products and activities. Competition is high not just from abroad, but also in our country. In wine field customers can choose from many products and wine producers should try hard to survive. Using marketing tools is in this field as need as in any other businesses and without them there is not a big chance to be successful. Marketing tool is a mean of communication with a customer and a customer plays the most important role. Using the right marketing tools can make your brand special – different from the others. Doing marketing research helps companies to know their target group - customers that really buy or want to buy their products. Asking the right question in marketing research can help them to use the right marketing tools. In many cases it means to spend marketing budget the way that will truly communicate with their target group. Then there is just a short way to be successful – in our case in wine field.